Zakat, Infak, Sedekah, Wakaf dalam Filantropi Islam - Linge, Abdiansyah; Ahmad, Upi Sopiah (YASIN, 2022)
One way to use wealth is to implement the concept of philanthropy, this is contained in the Qur'an and then clarified by Allah with the actualization of the Prophet Muhammad SAW, Philanthropy is a concept that already exists in Islam, which aims for goodness (al-birr), seeing the condition of the level of different social and economic aspects of society, the idea or concept of philanthropy is an alternative for a group of people to reduce social inequality between communities. The approach used in this paper is an empirical approach, namely a search based on existing findings. In this context, studies of the concept of Islamic Philanthropy become one way to empower the community in economic activities. This study focuses on the role of ZISWAF as a part of Philanthropy in Islam. The data collection technique used a literature review in the form of collecting books, written materials and references relevant to the theme of philanthropy as an instrument. Furthermore, an analysis of Islamic Philanthropy theories that have an impact on the economic activities of the community is carried out, which is expected to eventually build the concept of Islamic Philanthropy as an effort to reduce social inequality. Referring to the Qur'an and Hadith, philanthropy in Islam is an act of kindness based on faith which is charity. Philanthropy, as a charity, is a very fundamental ethical teaching in Islam. In general, the form of philanthropy in Islam is stated in the concept of zakat and shadaqah. The aim of building togetherness and reducing social inequality is inseparable from the distribution system. In Islam, there are two main distribution systems, namely commercial distribution and following the market mechanism and a distribution system that is based on aspects of community social justice.